2014
DOI: 10.1002/14651858.cd010965
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for chronic non-hypovolaemic hypotonic hyponatraemia

Abstract: Interventions for chronic non-hypovolaemic hypotonic hyponatraemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The role of vasopressin V2 receptor antagonists (vaptans) to improve hyponatremia and, thereby, mortality have produced discordant results [26]. A Cochrane analysis done on studies done up to 2017 suggested that there is no role for vaptans in chronic (defined as >48 h) hypervolemic hyponatremia as they could not find a consistent benefit in reducing mortality with vaptans [27]. However, the study population in those studies were vastly different from the sicker hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…The role of vasopressin V2 receptor antagonists (vaptans) to improve hyponatremia and, thereby, mortality have produced discordant results [26]. A Cochrane analysis done on studies done up to 2017 suggested that there is no role for vaptans in chronic (defined as >48 h) hypervolemic hyponatremia as they could not find a consistent benefit in reducing mortality with vaptans [27]. However, the study population in those studies were vastly different from the sicker hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focused on short-term outcomes such as normalization of SNa or overcorrection. Few studies evaluated the effect of vaptans stratified by volume status: hypervolemia or euvolemia [35,36]. Aggravation of hyponatremia can cause severe symptoms such as poor oral intake, general weakness or altered consciousness, leading to hospitalization.…”
Section: Remarksmentioning
confidence: 99%
“…Since hyponatremia in heart failure primarily occurs due to derangements of free water regulation, limiting free water intake may help; the American College of Cardiology/American Heart Association and European heart failure guidelines explicitly recommend this strategy for patients with stage D heart failure 3 , 4 . However, no available randomized data support this practice, and observational data suggest that fluid restriction has limited impact on hyponatremia in ADHF 14 . Guidelines also suggest employing fluid restriction in patients with diuretic resistance as an adjunctive therapy.…”
Section: When Fluid Restriction Is Helpful In the Management Of Decompensated Heart Failure In Hfref Patientsmentioning
confidence: 99%